Does High Stock Return Synchronicity Indicate High or Low Price Informativeness? Evidence from a Regulatory Experiment1. (12th October 2017) - Kan, Shuo; Gong, Stephen
Abstract: We investigate the link between stock return synchronicity and price informativeness by exploiting the Regulation SHO pilot program, which removed short‐selling price tests for randomly selected stocks ("pilot stocks") in May 2005. A difference‐in‐differences analysis reveals that relative to non‐pilot stocks, pilot stocks saw a significantly larger increase in both price informativeness and return synchronicity when the pilot program started, but such difference disappeared when Regulation SHO removed the short‐selling price tests for all stocks in July 2007. The results suggest that high return synchronicity reflects high, rather than low price informativeness.